(untitled) (Studia Prawnicze / The Legal Studies, 1984)
It is admissible to conclude marriage settlements consisting in expanding, limiting’ or excluding statutory joint property. It is not necessary, however, to conclude settlements restoring statutory system of matrimonial property rights as it is enough to dissolve a marriage settlement or to conclude a settlement quashing effects of the decision passed by the court on the basis of art. 52 of the family and guardianship code. When the spouses accept extended joint property and define their unequal. shares in joint property in marriage settlement, they may demand that the court establish unequal shares in joint property in view of the contribution of each of the spouses to the property. The spouses may settle this issue themselves. Marriage settlement has legal consequences for the parties. It has legal consequences for third persons only when they, before entering in legal transaction wjth the spouse, knew that the spouses had concluded marriage settlement. In such a case extended effectiveness of legal transaction occurs. Marriage settlements, although seldom concluded in practice, are of a positive character as they allow a certain group of married couples to accept a system of matrimonial property rights other than statutory one.